Allometric Relationships in the Mussel, Musculista senhausia from Cochin Backwaters - K., Shiny Sreedhar; C.K., Radhakrishnan (Fishery Technology, 2025)
The allometry of a population of Musculista senhausia (Benson) were studied during the period from February 1987 to June 1988. Monthly samples were taken from Cochin backand the allometric relationships between length and height, depth, total weight, flesh weight and shell weight were determined. The relationships are described by regression analysis of pairs of variables. Covariance analysis of the data revealed significant monthly differences in these relationships except in length-height and the factors causing these fluctuations are discussed.